Cancer Gene Profiling Methods and Protocols - Grützmann, Robert; Pilarsky, Christian (Springer New York, 2016)
This second edition volume brings together the experiences of leading scientists in the discipline of cancer gene profiling. Because cancer genes can be profiled in many different ways, Cancer Gene Profiling: Methods and Protocols, Second Edition explores different techniques and approaches needed to understand the key stages of cancer development, as using only one technique would be insufficient. This book provides readers with an overview of the state-of-the-art methods that will enable them to perform these experiments, and demonstrates the kind of analysis that is possible in our current biomedical research. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Thorough and cutting-edge, Cancer Gene Profiling: Methods and Protocols, Second Edition is a great resource for any student or practitioner with an interest in cancer gene profiling, and can be used in any well-equipped research laboratory
Keywords: Biomedicine; Cancer Research; Gene Expression; Medicine; Cancer research; Gene expression; Aufsatzsammlung